Modelling of propulsion shaft line and basic procedure of shafting alignment calculation - Vulić, Nenad (Array, 2008)
Summary: The main propulsion shafting is exposed to various operating conditions throughout the entire;;lifetime of a modern ship. The necessary condition for the shafting to withstand and survive all;;possible situations is its proper dimensioning and manufacture, as well as its assembly and testing;;onboard. Its alignment is of utmost importance during the assembly process itself.;;The aim of this paper is to present the shafting alignment calculation procedure in order to help the designer to understand the whole alignment process. Calculation presumptions, modelling of shafting parts, material properties and loading are given in detail. The advantages of the transfer matrix methods over the fi nite element methods in this particular case have been described.;;The important part is to establish the designed shafting elastic line onboard the ship, during the outfi tting in the shipyard. It is proposed in the conclusion that the presented matter be included into a future edition of the CRS Technical Rules